Low Paid Employment in Britain: Estimating State-Dependence and Stepping Stone Effects - Lixin Cai; Kostas G. Mavromaras; Peter J. Sloane (Institute for the Study of Labor (IZA), 2016)
Using 18 waves of the British Household Panel Study, this paper examines state dependence and stepping stone effects of low pay. A distinguishing feature is that five types of transition- not in the labour force (NILF), unemployment, self-employment, low pay and higher pay are modelled separately. The results show that both state dependence and stepping stone effects of low pay are present. However, there is no evidence to support a low-pay no-pay cycle. The introduction of the national minimum wage does not appear to have affected state-dependence and stepping stone effects of low pay.
Keywords: J24; J31; I21; 330; low pay; unemployment; state dependence; dynamic models